Penyesuaian Diri pada Orang Tua dengan Anak Down Syndrome - Erdi Istiadji; Ardelia Ajeng Wardhani (Fakultas Dakwah UIN KHAS Jember, 2024)
The birth of down syndrome children can affect parents' daily activities, the pattern of parental relationships with the surrounding environment, and parents' mental health. Parents must have selfadjustment in order to survive in these circumstances. This study aims to analyze the adjustment of parents with down syndrome children using theories from Siswanto. A person's self-adjustment can be seen through five indicators, namely accurate perception of reality, ability to cope with stress, having a positive self-image, the ability to express feelings, and good interpersonal communication skills. This research uses qualitative methods with a case study research design. The results showed that all five participants had been able to adjust to having a child with down syndrome, but with different stress coping strategies, namely emotional focus coping and problem focus coping.